The rational man versus the intuitive man: analogies between Rameau and Friedrich Nietzsche - Silva, Fernando Xavier (Universidade Estadual de Campinas, 2019)
It is a review of the works Nephew by Rameau de Denis Diderot (1713-1784), On Truth and Lie in the Extra-Moral sense by Friedrich Nietzsche (1873) and The Construction of the Sciences: Introduction to the Philosophy and Ethics of the Sciences by Gerárd Fourez (1995). The texts were read based on the following questions: What are the bases of knowledge support ?; What is the truth and whether it can be attained objectively; What is science and what does it represent in the search for truth and knowledge? and What are the possibilities of language in the search for knowledge? It was concluded that what Diderot characterizes as idiotism is similar to the moral values followed by the herd instinct in Nietzsche individuals. For Fourez, observation is always to represent and in representation, the true essence of the object is never obtained. Deconstructing concepts, apprehending the fluid and changing aspect of things and values, would be the main line of the texts dealt with in this work.